Analysis of central retinal microcirculation in glaucoma after neuroretinoprotective treatment - N.G. Glazko; A.E. Egorov (РМЖ "Клиническая офтальмология", 2021)
N.G. Glazko1, А.Е. Egorov1,2 1 Hospital for War Veterans No. 2, Moscow, Russian Federation 2 Pirogov Russian National Research Medical University, Moscow, Russian Federation Aim: to study the changes in microcirculation in patients with moderate primary open-angle glaucoma (POAG) receiving different neuroretinoprotective therapies. Patients and Methods: 50 patients (78 eyes) with moderate POAG and controlled IOP were enrolled. The study group included 25 patients (46 eyes) and the control group included 25 patients (32 eyes). Mean age was 79.5 years (77; 83). Before starting treatment and during the study, all patients underwent eye exams, i.e., visual acuity measurement, autorefractometry, slit lamp exam, eye fundus exam, IOP measurement, questioning to assess subjective vision, static automated perimetry, and optical coherence tomography angiography (OCTA) to evaluate foveal avascular zone / FAZ (area, perimeter, and circularity index). Six-month follow-up included 5 check point examinations. Modified trophic laser photocoagulation (tMLP) using a 810-nm diode laser on day 1 plus daily peribulbar injections of the water-soluble fraction s of polypeptides (Retinalamin) were performed in the study group. Conventional treatment for glaucomatous optic neuropathy (antioxidants, vasodilators, nootropic drugs, and retinoprotectors) was performed in the control group. Results: in the study group, FAZ area reduced by 33% immediately after the treatment, by 28.7% after 1 month, and by 16.8% after 6 months compared to baseline. In addition, FAZ perimeter reduced by 26.7%, 17.6%, and 8.1%, respectively, compared to baseline. No significant changes in visual acuity, visual field indices, and FAZ parameters were revealed. Moderate and strong correlation between the mean deviation (MD) and FAZ area was revealed in both groups irrespective of treatment type (rstudy=-0.6044, р<0.05; rcontrol=-0.8249, р<0.05). Conclusion: OCTA assesses central retinal microcirculation by FAZ parameters. The changes in FAZ parameters illustrate treatment efficacy and correlate with functional improvement (as demonstrated by visual field testing). Hence, it is recommended to monitor FAZ parameters when providing neuroretinoprotective therapy to evaluate its effectiveness. Keywords: optical coherence tomography angiography, primary open-angle glaucoma, glaucomatous optic neuropathy, neuroretinoprotection, modified trophic laser photocoagulation, foveal avascular zone. For citation: Glazko N.G., Egorov А.Е. Analysis of central retinal microcirculation in glaucoma after neuroretinoprotective treatment. Russian Journal of Clinical Ophthalmology. 2021;21(1):3–8. DOI: 10.32364/2311-7729-2021-21-1-3-8.